RELEVANSI KONSEP KAFA’AH DAN HAK IJBAR WALI DI ERA MODERN PERSPEKTIF MAZHAB HANAFIYAH DAN SYAFI’IYAH - Mahmudah Ridlwan; Isyrofah Tazkiyah Iroyna (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2023)
The purposes of this study are to find out the opinion of Hanafiyah and Syafi’iyah mazhab about kafâ’ah; and how kafâ’ah is applied by parents when doing ijbar on their daughther in the view of Islamic marriage law. This research is library research and content analysis approach is used to get answers the research problems. The conclusions are (1) The Hanafiyah dan Syafi’iyah mazhab agreed that kafâ’ah must be exist in a marriage, and must be emphasized is kafa’ah in terms of the religion of devotion to Allah swt and good morals. Kafa’ah in wealth is also emphasized by Hanafiyah mazhab, but Syafi’iyah mazhab more emphasized on religion and avoids disgrace; (2) According Islamic marriage law, the ijbar right is related to kafâ’ah, when parents must use kafâ’ah as one of the guardiansip requirements when making ijbar right for his daughter. With kafâ’ah it’s hoped that household life will be beneficial. Therefor, the concept of kafâ’ah as a condition for the guardian’s ijbar rights is still relevant today.